The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pen.22096
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a structured acrylic impact modifier and its application in toughening polyamide 6

Abstract: A series of poly(n‐butyl acrylate)/poly(methyl methacrylate‐co‐acrylic acid), i.e., poly(BA/MMA‐co‐AA), core‐shell structured modifiers with different contents of crosslinking agent allyl methacrylate and functional monomer were prepared, and its effects on mechanical properties of polyamide 6 (PA 6) blends were investigated. The modifiers were prepared at a solid content of 50 wt% by a seeded emulsion polymerization. Dynamic light scattering measurement showed that the particle grew without significant second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…This illustrated that the misaligned grains would have great growth advantage and can overgrow the well-aligned grains under special conditions. The findings of Zhou and our previous research [14,20] had validated this discovery. In order to explore the mechanism of competitive grain growth in DS, several important relationships of grain competitive growth have been analyzed as following.…”
Section: Grain Competitive Growth Mechanismsupporting
confidence: 86%
See 1 more Smart Citation
“…This illustrated that the misaligned grains would have great growth advantage and can overgrow the well-aligned grains under special conditions. The findings of Zhou and our previous research [14,20] had validated this discovery. In order to explore the mechanism of competitive grain growth in DS, several important relationships of grain competitive growth have been analyzed as following.…”
Section: Grain Competitive Growth Mechanismsupporting
confidence: 86%
“…5a, there was another different result for the grain competitive growth. Grain B may be overgrown by grain A, which has been confirmed by most researchers and our previous experimental results [20]. Therefore, the two grains could overgrow each other under different conditions for this converging relationship.…”
Section: Grain Competitive Growth Mechanismsupporting
confidence: 65%
“…Zhao et al prepared PBA‐poly(methyl methacrylate‐co‐acrylic acid) (PBMA) core/shell particles with narrow size distribution by semi‐continuous emulsion polymerization under monomer‐starving conditions to toughen a polyamide 6 (PA‐6) matrix, and found that the PA‐6‐PBMA blends were significantly tougher due to the good dispersion and adhesive interface between PBMA and PA‐6 .…”
Section: Discusionmentioning
confidence: 99%
“…Toughening modification of PA6 has always been a research hotspot because PA6 is sensitive to notch, which leads to low impact strength. To enhance its toughness, the utilization of tougheners is a common and effective method, such as core-shell particles, [7][8][9][10] rubbers, [11][12][13][14] and thermoplastic elastomers, [15][16][17] but the rigidity of modified PA6 is prone to be compromised. For example, with the addition of polyolefin elastomer-graft-maleic anhydride (POE-MAH), the modified PA6 showed a nearly 11-fold increase in impact strength compared to the original PA6, meanwhile, the yield stress dropped by nearly 50%.…”
Section: Introductionmentioning
confidence: 99%